Clinical analysis of 1,038 cases of odontogenic jawbone cysts - Chongli Du; Zeyu Wang; Duoduo Lan; Ruikun Zhu; Dong Wang; Hanying Wang; Chengao Wan; Tingyi Gao; Rui Han; Liang Liu; Kai Zhang (BMC Oral Health)
Abstract Background This study aims to analyse the clinical characteristics of different types of odontogenic jawbone cysts (OJCs) and to provide a theoretical basis for prevention and clinical treatment. Methods Data from 1,038 patients with OJCs were collected, and relevant information, such as sex, age, clinical symptoms and signs, imaging data, number of lesions, lesion location, pathological diagnosis, clinical treatment and prognosis, was statistically analysed. Results According to the World Health Organization (WHO) classification of OJCs in 2022, the highest incidence rate was observed for radicular cysts (RCs), accounting for 58.96% of the total number of cases, followed by dentigerous cysts (DCs), accounting for approximately 23.22% of cases. lateral periodontal cysts (LPCs) and calcifying odontogenic cysts (COCs) comprised the lowest number of cases. The age distribution of patients was between 4 and 89 years, and the high incidence age group was youth and middle age, accounting for 66.67% of the total number of cases. The male-to-female ratio of patients was 1.51:1, and there was a statistically significant difference between the sexes(p < 0.05).In terms of the site of incidence, odontogenic keratocysts (OKCs) were prevalent in the mandibular molar region. In addition, mandibular ramus, inflammatory collateral cysts (ICCs) and dentigerous cysts (DCs) were more common in the mandibular third molar, and radicular cysts (RCs) and calcifying odontogenic cysts (COCs) were prevalent in the maxillary anterior region. On imaging, 955 (92.0%) lesions were solitary, and 83 (8.0%) were multiple. The treatment included four types of surgery, including simple curettage, marsupialization, marsupialization followed by secondary curettage, and partial resection of the jaw, and a total of 921 patients were followed up, with a recurrence rate of 2.82%. Conclusions OJCs are more common in males than in females, and a statistically significant difference is observed in the most prevalent types of cysts occurring at different ages and in various regions of the jawbone (p < 0.05). Early diagnosis should be made with the help of X-rays, age, location, and clinical symptoms. In addition, appropriate treatment methods should be selected, and long-term follow-up observation is needed.